The Effect of Game Therapy on Anxiety of Child Patients at the Dental Polyclinic of Besulutu Health Center in Konawe Regency - Romantika, I Wayan; Riska, Riska; Firman, Firman (PT. Nursing Genius Care, 2024)
Background: Dental anxiety is the fear that something dreadful may occur before to a dental appointment or procedure where dental anxiety increases when seeing the operator preparing equipment for a tooth extraction procedure such as forceps and syringes. Controlling anxiety is the most important thing in managing children's behavior in dental treatment. Delays in treatment can result in worsening oral disease levels and increase anxiety in children visiting the dentist. The purpose of this study was to determine the effect of game therapy on anxiety in child patients at the Dental Polyclinic of Besulutu Health Center in Konawe Regency. Methods: A sample of 32 children who visited the Dental Polyclinic of Besulutu Health Center participated in the pre-experimental study using the one group pretest-posttest design approach. Unintentional sampling was the method employed for sampling. Game therapy was one of the independent variables in this study, while anxiety was the dependent variable. The Wilcoxon test was used to examine the data. Results: The study's findings suggest that game therapy for children at the Dental Polyclinic of Besulutu Health Center in Konawe Regency has an impact on their anxiety levels. 0.000 was the ρ value that was obtainedfrom the analysis utilizing the Wilcoxon test. Conclusion: It is recommended that health centers provide policies on play therapy for children undergoing treatment either at the dental polyclinic or other polyclinics